Diet as Self-Care in Chronic Kidney Patients in Patient-Centered Care: Scoping Review - Siti Nur Aida; Wahyu Hidayati; Meira Erawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Chronic kidney disease (CKD) is a progressive condition that affects the quality of life of millions of people worldwide. While diet is essential in slowing disease progression and preventing complications, its implementation as self-care often faces barriers especially when patient preferences and context are overlooked. Most existing studies focus on clinical outcomes, with limited attention to how dietary practices are applied within a patient-centered approach that considers cultural, social, and psychological factors. This scoping review aims to map the existing evidence on how diet is implemented as a form of self-care in patients with CKD, within the framework of patient-centered care. This article uses three databases PubMed, EBSCO, and science direct with the keywords “diet,” “self care,” “self management,” and “chronic kidney disease” combined using Boolean AND and OR operators. Articles is in full text, in English, open access, published between 2015 and 2025, with quantitative, qualitative, descriptive, secondary analysis, quasi-experimental, or mixed methods research designs. From the 1,935 articles found, gradual screening was carried out until 7 relevant articles were obtained and further analyzed according to the PRISMA-Scr guidelines. Seven relevant articles showed that adherence to CKD diet was influenced by health literacy, self-efficacy, social support, and economic and cultural barriers. Experience-based interventions, goal setting, self-monitoring, and digital technologies such as health apps showed effectiveness in improving dietary adherence and patient quality of life. Collaborative approaches and family support were also shown to be important in strengthening the success of dietary interventions. Diet as part of self-care in CKD patients not only has clinical benefits, but also contributes to improving psychosocial well-being. A holistic approach that considers social, cultural, and emotional aspects is needed for dietary interventions to be more effective and sustainable in patient-centered practice.